2019
DOI: 10.3390/s19081941
|View full text |Cite
|
Sign up to set email alerts
|

Monocular Visual-Inertial Odometry with an Unbiased Linear System Model and Robust Feature Tracking Front-End

Abstract: The research field of visual-inertial odometry has entered a mature stage in recent years. However, unneglectable problems still exist. Tradeoffs have to be made between high accuracy and low computation for users. In addition, notation confusion exists in quaternion descriptions of rotation; although not fatal, this may results in unnecessary difficulties in understanding for researchers. In this paper, we develop a visual-inertial odometry which gives consideration to both precision and computation. The prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…An uncertainty assessment is essential for evaluating the reliability of the estimated camera trajectory in VO. While traditional VO approaches often provide an analytical formula for uncertainty, this remains an open challenge for machine learning-based VO methods [ 40 ].…”
Section: Research Challenges In Monocular Visual Odometrymentioning
confidence: 99%
“…An uncertainty assessment is essential for evaluating the reliability of the estimated camera trajectory in VO. While traditional VO approaches often provide an analytical formula for uncertainty, this remains an open challenge for machine learning-based VO methods [ 40 ].…”
Section: Research Challenges In Monocular Visual Odometrymentioning
confidence: 99%
“…Considering the fact that the measurements of vehicle kinematic error originate from the vehicle velocity, angular rate, and the characteristics of the vehicle relative kinematic errors between two consecutive camera states, the method using a kinematic error measurement model for the vehicle has different parameter configurations in practical application. Therefore, following Equation (15), the tunable parameter configurations of ACK-MSCKF are as shown in Table 1. The limitation of the above relative kinematic error measurement model for the vehicle derives from the assumption that the vehicle velocity is constant for low-speed motion between two consecutive camera states.…”
Section: Measurements Of Vehicle Relative Kinematic Errormentioning
confidence: 99%
“…It is widely used in the pose estimation of mobile robots owing to the advantages of favorable robustness, small size and low cost. VIO mainly consists of filter-based methods, including the Multi-Sensor Fusion Approach (MSF) [ 8 ], the Robust Visual-Inertial Odometry (ROVIO) [ 9 ], the Multi-State Constraint Kalman Filter (MSCKF) [ 10 ], Stereo-MSCKF [ 11 ], S-MSCKF [ 12 ], the Robocentric Visual-Inertial Odometry (R-VIO) [ 13 ], Schmidt-MSCKF [ 14 ], the Lightweight Hybrid Visual-Inertial Odometry (LARVIO) [ 15 , 16 ] and optimization-based methods including the Open Keyframe-based Visual-Inertial SLAM (OKVIS) [ 17 ], ORB-SLAM-VI [ 18 ], VINS-Mono [ 19 ], PL-VIO [ 20 ], ICE-BA [ 21 ], VI-DSO [ 22 ], VINS-Fusion [ 23 , 24 ], Basalt [ 25 ] and ORB-SLAM3 [ 26 ]. A detailed review of the VIO methods can be found in the literature [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on estimating a vehicle’s motion by fusing the measurements from a monocular camera and an inertial measurement unit (IMU). This task—the well-known monocular vision-aided inertial navigation system (VINS) problem—has drawn great interest in the robotic community (e.g., [1,2,3,4,5,6,7]) for many reasons.…”
Section: Introductionmentioning
confidence: 99%